Jumps and Information Flow in Financial Markets - Lee, Suzanne S. (Review of Financial Studies, 2012)
This article investigates the predictability of jump arrivals in U.S. stock markets. Using a new test that identifies jump predictors up to the intraday level, I find that jumps are likely to occur shortly after macroeconomic information releases, such as the Federal Reserve announcements, nonfarm payroll reports, and jobless claims, as well as market index jumps. I also find firm-specific jump predictors related to earnings releases, analyst recommendations, past stock jumps, and dividend dates. Evidence suggests that distinguishing systematic jumps from idiosyncratic jumps is possible using the characteristics of jump predictors. Finally, I present a short-term jump size clustering. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.